Integrating STEAM Education through Shibori Art: Improving Self-Love and Self-Esteem Among Women - Rahmawati Rahmawati; Maria Cornelia Wara Candrasari; Cecilia Tridjata; Febby Bunga Permata Sumardi; Nanda Arumita; Ahmad Rayhan (Jurnal Pendidikan Abad Ke-21, 2025)
This study aimed to discuss the effectiveness of Shibori creative art in fostering self-love and self-esteem as a means to empower women's roles. The study was conducted at RPTRA Kayu Manis, North Jakarta, with Shibori art treatment. The number of respondents involved was 10 people, aged 25-50 years, women with junior and high school education levels. Data were collected through observation, in-depth interviews, and analysis of the participants' work and quantitative data from pre-test and post-test experiments on the self-love measurement scale with a reliability value of the self-love measurement scale, r = 0.89 and a validity value of Cronbach's Alpha 0.7, and a self-esteem measurement scale with a reliability value of the self-esteem measurement tool r = 0.82 and a validity value of Cronbach's Alpha = 0.81. The paired T-test results showed significant improvements in both aspects, with self-love increasing by 4.2 points (t=6.89, p0.001) and self-esteem increasing by 5.3 points (t=9.81, p0.001), with a large effect size (Cohen's d 2). Supporting factors such as freedom of expression, meditative nature, and pride in one's work played a crucial role. However, the complexity of the technique, the tendency towards self-judgment, and time constraints can hinder its effectiveness. For optimization, recommendations include modifying the technique (e.g., using a simpler method), integrating cognitive reflection, and grouping participants according to ability level.